Mental and Emotional Problems among Preschool-Aged Children Experiencing Sibling Rivalry: Case Study - Ruminem, Ruminem; Saputra, M. Aldi; Puspa Sari, Rita; Widiastuti, Ida Ayu Kade (Fakultas Kedokteran, 2025)
AbstractIntroduction: Sibling rivalry in preschool-aged children may lead to various consequences, including negative impacts on the children themselves, such as aggression, tantrums, emotional instability, excessive reactions, low self-confidence, and feelings of resentment toward siblings. It may also affect sibling relationships, manifested by aggressive behavior, unwillingness to share, competitive attitudes, lack of cooperation, frequent tattling, dominance over siblings, and modeling of negative behaviors. Objective: This study aimed to describe the mental–emotional problems of preschool-aged children experiencing sibling rivalry.. Methods: This study employed a descriptive research design with a case study approach. The subjects were preschool-aged children attending Tunas Rimba 1 Kindergarten who experienced sibling rivalry, along with their parents, involving a total of six participants. The research instruments included a Sibling Rivalry Questionnaire and the Mental–Emotional Problems Questionnaire (KMME). Data were analyzed using descriptive explanatory analysis.Results: The findings revealed that all participants (six children) experienced high levels of sibling rivalry, characterized by aggressive behavior, competition, and feelings of jealousy toward siblings. Based on the KMME assessment, five participants were categorized as having a possible risk of mental–emotional problems, indicated by behaviors such as unexplained anger, excessive fear, and confused behavior, while one participant was categorized as normal. Conclusion: Children experiencing sibling rivalry may be at risk of developing mental–emotional problems, with the majority classified as having a possible risk. It is recommended that parents actively seek information regarding the impact of sibling rivalry on children and engage in counseling to prevent further mental–emotional problems